Automated retinal vessel detection - Zhang, Xinyi (2017)
As the first step of automatic retina image analysis, automatic retinal vessels segmentation is a meaningful and important topic for auto diagnosis. There are several algorithms currently can realise automatic retinal vessels segmentation with a relatively high accuracy. Based on the existing research, this thesis chooses artificial neural network (ANN) as the main segmentation algorithm followed by post-processing method to achieve vessels segmentation.